Controlled Synthesis of Poly(p‐phenylene) Using a Zincate Complex, tBu4ZnLi2. Issue 14 (10th May 2017) - Ochiai, Yuto; Goto, Eisuke; Higashihara, Tomoya
Abstract : Well‐defined poly(2, 5‐dihexyloxyphenylene‐1, 4‐diyl) (PPP) is successfully synthesized by Negishi catalyst‐transfer polycondensation using dilithium tetra( tert ‐butyl)zincate. The PPP samples possess molecular weight values in the range of 2100–22 000 and molar mass dispersity values in the range of 1.09–1.23. Abstract : Well‐defined poly(2, 5‐dihexyloxyphenylene‐1, 4‐diyl) (PPP) is successfully synthesized by the Negishi catalyst‐transfer polycondensation (NCTP) using dilithium tetra( tert ‐butyl)zincate ( t Bu4 ZnLi2 ). The obtained PPP possesses the number‐averaged molecular weight ( M n ) values in the range of 2100–22 000 and the molar‐mass dispersity ( Ð M ) values in the range of 1.09–1.23. In addition, block copolymers containing PPP and poly(3‐hexylthiophene) (P3HT) segments (PPP‐ b ‐P3HT) are synthesized to confirm the feasibility of chain extension between the different monomers based on NCTP.